Questioning assumptions of trophic behavior in a broadly ranging marine predator guild. Issue 5 (5th February 2019) - Shipley, Oliver N.; Olin, Jill A.; Power, Michael; Cerrato, Robert M.; Frisk, Michael G.
Abstract : We evaluated whether existing assumptions regarding the trophic ecology of a poorly‐studied predator guild, northwest (NW) Atlantic skates (family: Rajidae), were supported across broad geographic scales. Four hypotheses were tested using carbon (δ 13 C) and nitrogen (δ 15 N) stable isotope values as a proxy for foraging behavior: 1) species exhibit ontogenetic shifts in habitat and thus display a shift in 13 C with differential use of the continental shelf; 2) species exhibit ontogenetic prey shifts (i.e. from smaller to larger prey items) and become enriched in 15 N; 3) individuals acquire energy from spatially confined local resource pools and exhibit limited displacement; and 4) species exhibit similarly sized and highly overlapping trophic niches. We found some evidence for ontogenetic shifts in habitat‐use (δ 13 C) for thorny and little skate and diet (δ 15 N) of thorny and winter skate and hypothesize that individuals exhibit gradual trophic niche transition, especially in δ 15 N space, rather than a clear and distinct shift in diet throughout ontogeny. Spatial isoscapes generated for little, thorny, and winter skate highlighted distinct spatial patterns in isotopic composition across the coastal shelf. For little and thorny skate, patterns mimicked expected spatial variability in the isotopic composition of phytoplankton/POM, suggesting limited displacement and utilization of spatially confined resource pools. Winter skate, however, exhibited a much narrower range of δ 13 C and δ 15 N values, suggesting individuals may use resources from a more confined latitudinal range. Although high total trophic niche overlap was observed between some species (e.g. little and thorny skate), sympatric species (e.g. little and winter skate) exhibited a degree of trophic niche separation. These findings offer new insight into the trophic dynamics of a poorly‐studied, vulnerable group of predators, and highlight a need to re‐examine assumptions pertaining to aspects of their ecology.